1996
DOI: 10.1002/(sici)1096-9861(19960122)364:4<609::aid-cne2>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Local circuit neurons in the medial prefrontal cortex (areas 24a,b,c, 25 and 32) in the monkey: II. Quantitative areal and laminar distributions

Abstract: The companion paper (Gabbott and Bacon [1996] J. Comp. Neurol.) describes the morphology of calretinin (CR)-, parvalbumin (PV)-, calbindin (CB)-, and GABA-immunoreactive neurons, and NADPH diaphorase-reactive cells, in the medial prefrontal cortex (mPFC; areas 24a, 24b, 24c, 25 and 32) of the adult monkey. Since these local circuit neurons play crucial functional roles, the aim of this study was to provide supportive quantitative data defining their areal and laminar distribution in mPFC. The numerical densiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
76
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 184 publications
(89 citation statements)
references
References 85 publications
13
76
0
Order By: Relevance
“…More recently, it has been observed that, in the primate principal sulcus (PS; area 46), PV-immunoreactive (ir) neurons are concentrated in the middle layers, are non-pyramidal, and classified as either wide arbor (basket) or chandelier cells (Williams et al 1992). Furthermore, there is evidence that, in the monkey prefrontal cortex, the different calcium-binding proteins, PV, calbindin D-28K, or CR, are segregated in populations of local circuit neurons that have distinct laminar distribution patterns (Conde et al 1994;Gabbott and Bacon 1996;Lund and Lewis 1993).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…More recently, it has been observed that, in the primate principal sulcus (PS; area 46), PV-immunoreactive (ir) neurons are concentrated in the middle layers, are non-pyramidal, and classified as either wide arbor (basket) or chandelier cells (Williams et al 1992). Furthermore, there is evidence that, in the monkey prefrontal cortex, the different calcium-binding proteins, PV, calbindin D-28K, or CR, are segregated in populations of local circuit neurons that have distinct laminar distribution patterns (Conde et al 1994;Gabbott and Bacon 1996;Lund and Lewis 1993).…”
Section: Introductionmentioning
confidence: 93%
“…The laminar distribution of PV-ir and CR-ir cells in the PS reported here was also similar to a previous study in the rhesus monkey (Dombrowski et al 2001). Another report has shown similar laminar distribution of PV-ir and CR-ir cells in other prefrontal cortical regions, anterior cingulate (area 24), prelimbic (area 32), and infralimbic (area 25) cortices of female cynomolgus monkeys (Gabbott and Bacon 1996). Dombrowski et al (2001), however, reported fewer CR-ir cells than PV-ir cells in area 46 of rhesus monkeys in contrast to our study where the number of CRir cells exceeds the number of PV-ir cells.…”
Section: Plasticity Associated With Prior Pcp Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in mice the majority of cortical GABA neurons are born in the ganglionic eminences, whereas this region contributes only about a third of cortical GABA neurons in humans (Anderson et al 1997;Letinic et al 2002). Together, these findings may explain why the density of PVpositive cells clearly exceeds that of CR-positive cells in rodent cortex (Gabbott et al 1997), while in primate DLPFC CR-positive cells outnumber PV-positive cells by 2:1 (CondØ et al 1994;Gabbott and Bacon 1996). Maturational differences among subtypes of GABA neurons are also evident postnatally.…”
Section: Specificity Of Cortical Gaba Neurotransmissionmentioning
confidence: 99%
“…(Gabbott and Bacon, 1996). This simulation was used to shed light on A c c e p t e d M a n u s c r i p t 14 the relative contribution of various interneuron subtypes to the maintenance and stability of WM representations.…”
Section: Computational Implementationmentioning
confidence: 99%